Identifikasi Bahaya dan Risiko Keselamatan dan Kesehatan Kerja pada Industri Tahu APU - Taufikah Mahmudah; Wartini Wartini; Nur Ani; Nine Elissa Maharani (KOLONI, 2026)
This study was motivated by the high potential hazards and low implementation of risk control measures in small and medium-sized tofu industries, which frequently lead to occupational accidents. The purpose of this study was to identify hazards, assess risk levels, and determine appropriate risk control measures at the APU Tofu Factory MSME. This research employed a quantitative descriptive method with a case study approach. Data were collected through direct observation, interviews, and document reviews across nine stages of the tofu production process. Data analysis was conducted using the Hazard Identification and Risk Assessment (HIRA) method. Data validity was ensured through method triangulation. The results identified 53 potential hazards consisting of physical, ergonomic, mechanical, biological, and chemical hazards. Physical hazards were the most dominant type (52.8%), particularly slippery floors, heat exposure, and boiling steam exposure. Risk assessment showed that 36 risks (67.9%) were categorized as medium risk, 11 risks (20.8%) as high risk, and 6 risks (11.3%) as low risk. The dominant risks included slips and falls, musculoskeletal disorders, burns, and occupational heat stress. This study recommends risk control measures through engineering controls (drainage system repair), administrative controls (work rotation and occupational safety training), and the use of appropriate standard personal protective equipment (PPE). These findings are expected to serve as a basis for developing occupational safety and health systems in the tofu industry MSME sector.